Correlates of Concurrent Sexual Partnerships among Young, Rural African American Men. (July 2015) - Kogan, Steven M.; Cho, Junhan; Barnum, Stacey C.; Brown, Geoffrey L.
Objective: We investigated the social, behavioral, and psychological factors associated with concurrent (i.e., overlapping in time) sexual partnerships among rural African American young men with a primary female partner. Methods: We recruited 505 men in rural areas of southern Georgia from January 2012 to August 2013 using respondent-driven sampling; 361 reported having a primary female partner and participating only in heterosexual sexual activity. Men provided data on their demographic characteristics and HIV-related risk behaviors, as well as social, behavioral, and psychological risk factors. Results: Of the 361 men with a primary female partner, 164 (45.4%) reported concurrent sexual partners during the past three months. Among the 164 men with a concurrent sexual partner, 144 (92.9%) reported inconsistent condom use with their primary partners, and 68 (41.5%) reported using condoms inconsistently with their concurrent partners. Having concurrent sexual partnerships was associated with inconsistent condom use, substance use before sex, and self-reported sexually transmitted infections (STIs). Bivariate correlates of concurrent sexual partnerships included incarceration, substance use, early onset of sexual activity, impulsive decision-making, and masculinity attitudes (i.e., men's adherence to culturally defined standards for male behavior). In a multivariate model, both masculinity ideology and impulsive decision-making independently predicted concurrent sexual partnerships independent of other risk factors. Conclusion: Masculinity attitudes and impulsive decision-making are independent predictors of concurrent sexual partnerships among rural African American men and, consequently, the spread of HIV and other STIs. Developing programs that target masculinity attitudes and self-regulatory skills may help to reduce concurrent sexual partnerships.